A Case of Disseminated Cryptococcal Infection and Concurrent Lung Tuberculosis in a Patient under Steroid Therapy for Interstitial Pneumonia - Aoi Kuroda; Sadatomo Tasaka; Kazuma Yagi; Takao Mochimaru; Tetsuo Tani; Ho Namkoong; Kyuto Tanaka; Yusuke Suzuki; Mami Hatano; Naoki Hasegawa; Yasunori Okada; Tomoko Betsuyaku (Case Reports in Pulmonology)
Both disseminated cryptococcal infection and tuberculosis occur in hosts with impaired cell-mediated immunity, but there have been few reports about the concurrent infections in patients without human immunodeficiency virus infection. A 64-year-old man, who had been taking corticosteroids for interstitial pneumonia, was diagnosed with disseminated cryptococcal infection. While the patient was receiving anticryptococcal therapy, pulmonary tuberculosis also emerged. The patient developed acute exacerbation of interstitial pneumonia and passed away. Based on the patient’s clinical course, serial computed tomography images, and autopsy results, we believe that the preceding several months of corticosteroid treatment might have contributed to these coinfections in the lungs already vulnerable due to underlying fibrosis.